Techniques for the recovery of volatile aroma compounds from biochemical broth: A review. (22nd March 2018) - Lukin, Ilya; Merz, Juliane; Schembecker, Gerhard
Abstract: Flavours, fragrances, or aromas are valuable chemicals, with a broad range of industrial applications. The consumer's preference for 'naturally' manufactured aromas drives the development of biochemical production, which requires suitable product recovery. In this study, different industrially established recovery techniques, their advantages and limitations, and their possible application for aroma recovery from crude fermentation broth are reviewed. Among several techniques discussed, absorption, adsorption, and pervaporation appear to be particularly suitable for the recovery of aromas from highly diluted biochemical mixtures. Abstract : Application of the aroma recovery techniques at different positions of the manufacturing process.